Front Cover: Tailored Charge Transfer Kinetics in Precursors for Organic Radical Batteries: A Joint Synthetic‐Theoretical Approach (ChemSusChem 2/2023). Issue 2 (3rd January 2023) - Zens, Clara; Friebe, Christian; Schubert, Ulrich S.; Richter, Martin; Kupfer, Stephan
Abstract : The Front Cover shows the charge transfer from TEMPO to the thiophene backbone moiety within organic radical batteries. The wells illustrate the calculated potential energy surfaces on which the charge transfer is based. Within the wells the charge—represented by the waves—is localized. Within the polymer the thiophene backbone is the charge conductor, hence the water (charge) can flow from well to well, while the waves from the TEMPO well can only splash over into the thiophene well. The charge transfer is further enhanced by an applied voltage, represented by the moon. The molecular moieties framed by the TEMPO and the thiophene are the linkers used to attach the TEMPO to the thiophene backbone. More information can be found in the Research Article by C. Zens et al .